ANALISIS KEMAMPUAN GURU DALAM MENYUSUN KARYA TULIS ILMIAH DI PUJUNGAN KABUPATEN MALINAU KALIMANTAN UTARA - Agustinus Toding Bua; Efraim Bavo Priyana; Dewi Retnaningati (Journal of Educational Review and Research, 2023)
Professional teachers are required to continue to develop themselves in accordance with the times, science and technology, as well as the needs of society, including the need for quality human resources and have the capability to be able to compete in regional, national or international forums. One of the abilities that a teacher in the academic field must have is compiling scientific papers. The preparation of by teachers is closely related to their efforts to improve learning processes and outcomes as well as supporting factors in the promotion process. Therefore, this research article aims to improve the ability to write scientific papers for teachers in Pujungan, Malinau District, North Kalimantan Province. In this study the analysis of the teacher's ability to compose scientific papers was processed through an assessment of the research report documents that had been prepared. Furthermore, the data were analyzed in a quantitative descriptive manner. The research results show that 6 of the 8 aspects of ability analyzed were included in the less category with the lowest score in the aspect of "Analyzing research data comprehensively", namely with a value of 30. The other 2 aspects were included in the sufficient category, namely the aspect of "Using the Writing Format Correctly" with a value of 65 and "Good use of language" with a value of 60.